The glycyl-l-histidyl-l-lysine-Cu2+ tripeptide complex attenuates lung inflammation and fibrosis in silicosis by targeting peroxiredoxin 6 - Yiding Bian; Mingming Deng; Jia Liu; Jiaye Li; Qin Zhang; Zilin Wang; Liwei Liao; Jinrui Miao; Ruixia Li; Xiaoming Zhou; Gang Hou (Redox Biology, 2024)
Silicosis is the most common type of pneumoconiosis, having a high incidence in workers chronically exposed to crystalline silica (CS). No specific medication exists for this condition. GHK, a tripeptide naturally occurring in human blood and urine, has antioxidant effects. We aimed to investigate the therapeutic effect of GHK-Cu on silicosis and its potential underlying molecular mechanism. An experimental silicosis mouse model was established to observe the effects of GHK-Cu on lung inflammation and fibrosis. Moreover, the effects of GHK-Cu on the alveolar macrophages (AM) were examined using the RAW264.7 cell line. Its molecular target, peroxiredoxin 6 (PRDX6), has been identified, and GHK-Cu can bind to PRDX6, thus attenuating lung inflammation and fibrosis in silicosis mice without significant systemic toxicity. These effects were partly related to the inhibition of the CS-induced oxidative stress in AM induced by GHK-Cu. Thus, our results suggest that GHK-Cu acts as a potential drug by attenuating alveolar macrophage oxidative stress. This, in turn, attenuates the progression of pulmonary inflammation and fibrosis, which provides a reference for the treatment of silicosis.